ANALISIS PELAKSANAAN PENERIMA PROGRAM KELUARGA HARAPAN MELALUI KARTU INDONESIA PINTAR PADA SISWA KELUARGA KURANG MAMPU DI DESA NANGA KALIS - Afrilia Dwi Suparti; Imran Imran; Iwan Ramadhan (Universitas Tanjungpura, 2021)
AbstractThis study aimed to described the implementation of the recipients of the Family Hope Program (Program Keluarga Harapan) through the Smart Indonesia Card (KIP) for Underprivileged Family Students in Nanga Kalis Village and analysed the Implementation Constraints of the Recipients of the Expected Family Program through the Smart Indonesia Card for Underprivileged Families Students in Nanga Kalis Village. This research was used qualitative descriptive method. The data collection process was carried out through observation, interviews and documentation. Then, the stages of data analysis in the form of data collection, data reduction, data presentation, and verification/drawing conclusions. The sample of this research was taken from the beneficiaries were 3 families, 1 village secretary and 1 assistant. The results obtained in the field are as follows: 1) The implementation of the Family Hope Program Recipients through the Smart Indonesia Card for Underprivileged Families Students in Nanga Kalis Village, is by selecting students who are viewed from the student's family data as a requirement to obtain KIP. Furthermore, assistance is carried out by one person to direct parents/students in disbursing funds from KIP. 2) Obstacles in implementing the Family Hope Program Recipients through Smart Indonesia Cards for Underprivileged Families Students in Nanga Kalis Village, are delays in disbursing KIP funds which result in student facilities being hampered from being fulfilled.Keywords: Implementation, Family Hope Program, Smart Iindonesia Card